Relationship between nutrition intake, eat patterns and nutrition knowledge with nutritional status of santri in At-Thayyibah Orphan Boarding School Sukabumi - Nurwulan, Endah; Furqan, Muhammad; Safitri, Debby Endayani (ARGIPA (Arsip Gizi dan Pangan), 2018)
Nutritional problems are complex that are influenced by direct and indirect factors. Nutrition intake, food pattern, and nutritional knowledge are factors that affect nutrition indirectly. Adolescents require good nutrition intake because at that time they are experiencing growth both physically and physiologically, so inadequate intake will lead to slow growth. This study aimed to determine the relationship between nutrient intake, food pattern, and nutritional knowledge with the nutrition status of santri at the At-Thayyibah Islamic Orphan Boarding School in Sukabumi. The study design in this study was cross sectional and the sampling technique used was purposive sampling with a total of 76 subjects aged 13-18 years. From this study there was no significant relationship between nutrient intake (p> 0.05), diet (p> 0.05) and nutritional knowledge (p> 0.05) with nutritional status.